International Human Resource Management - Reiche, B. Sebastian; Tenzer, Helene; Harzing, Anne-Wil (London ; Thousand Oaks, California : SAGE Publications Ltd, 2023)
"Written by leading experts in the field, this bestselling textbook has guided over 25,000 students across 130 countries through their International Human Resource Management studies. Retaining its critical edge, academic rigour and breadth of coverage, the sixth edition has been thoroughly updated to include cutting-edge content on the Covid-19 pandemic, digitalization and artificial intelligence (AI)."--Back cover
Previous edition: 2019.
Includes bibliographical references and index.
Keywords: International business enterprises -- Personnel management; Personnel management; Personnel management; International business enterprises -- Personnel management